Solitary dermal cylindroma: a rare case report - Wahyu Tri Widayati; . Irianiwati (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2019)
Dermal cylindromas are rare benign skin appendageal tumors that has two clinical presentation, solitary and multiple form. The diagnosis is unusual.However, it must be considered in clinical practice.A 51-year-old woman hadpainless nodule on right arm. Skin examinatipn revealedtwo fragmented nodules, 1x0.5x0.5cm, tan to white, and rubbery. Histopathological findings revealed a well demarcated and an unencapsulated epithelial dermal tumor, composed of numerous oval and polygonal nests molded into a "jig-saw" or "mosaic" appearance at low power. The nests of cells were composed of basaloid cells with scant cytoplasm and hyperchromatic nuclei and paler cells at the center. Nests of epithelial cells were surrounded and penetrated by a thickened band of basement membrane material that was PAS-positive. Immunohistochemistry (IHC) staining with p63 showed positive staining on basaloid cells. Langerhans dendritic cells in the surrounding nests stained positive with CD1a. Solitary dermal cylindroma occurred sporadically in patients without family history of cutaneous cylindromas.Combination of morphologic, histochemystry and immunohistochemystry staining were needed for accurate diagnosis.